The Influences of Environmental Knowledge and Awareness towards Electric Car Purchase Intention Mediated by Green Purchase Attitude - Febrian, Lia; Ramli, Yanto (ARE Publisher, 2024)
Objectives: The objectives to this study are to determine the effect of environmental knowledge and awareness on consumers’ intention to purchase electric car, emphasizing the mediating role of green purchase attitude. The research aims to identify factors influencing the adoption of environmentally friendly transportationMethodology: A comprehensive quantitative approach was employed, with data collected from 101 respondents, specifically parents using vehicles for school transportation. A structured questionnaire assessed variables like environmental knowledge, awareness, and purchase intentions. Data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) and additional advanced statistical techniques to explore interrelations among constructs.Conclusion: The results reveal that only environmental awareness significantly influences green purchase attitude, which mediates its impact on green purchase intention while environmental knowledge don’t have any significant impact towards green purchase attitude and no mediating effect toward green purchase intention.